(untitled) (Journal of Hama University, 2022)
This research aims to study the relationship between public expenditure on telecommunications infrastructure in the Syrian governorates and achieving the requirements of sustainable economic development, telecommunications and technology have an impact on the process of economic development, in addition to being one of the very important factors affecting the productivity and returns of economic projects as well for success Competitive Modern Economy. The time series data for these variables were collected for the period (1988-2019) and were subjected to a statistical economic and financial study that began by analyzing the rates and growth rates and components of these variables, followed by a study of the stability of the time series, and finally the long-term co-integration equations for public expenditure on on telecommunications infrastructure in the Syrian governorates were estimated using ARDL model: Self-regression model for distributed time gaps. The results of the study showed the existence of a long-term relationship between sustainable economic development as a dependent variable and public expenditure on telecommunications infrastructure in the Syrian governorates as independent variables.